2021
DOI: 10.1016/j.jacr.2021.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Journal Scholarly Activity Among Female Contributors

Abstract: As a result of the coronavirus disease 2019 (COVID-19) pandemic, faculty members in medicine shifted their academic work to the home environment. Simultaneously, schools and childcare facilities closed, resulting in increased responsibilities and competing demands on working parents. Before the pandemic, women in academic medicine reported spending 8.5 more hours per week on domestic tasks and childcare than their partners and were more likely to take time off because of childcare needs if their partners worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…For example, since COVID-19 emerged as a high-profile, and very publishable subject, it is possible that it was easier for men, who are still more likely to be in leadership and well-funded positions in academia to pick up the topic quickly. Also, women were less likely to function as expert reviewers on articles related to COVID-19, [6][7][8] known to potentially exacerbate a pre-existing gender bias in the peer-review and publishing process. [22][23][24] These might contribute to a vicious cycle that hindered access to COVID-19 publishing especially for women in the early stages of their career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, since COVID-19 emerged as a high-profile, and very publishable subject, it is possible that it was easier for men, who are still more likely to be in leadership and well-funded positions in academia to pick up the topic quickly. Also, women were less likely to function as expert reviewers on articles related to COVID-19, [6][7][8] known to potentially exacerbate a pre-existing gender bias in the peer-review and publishing process. [22][23][24] These might contribute to a vicious cycle that hindered access to COVID-19 publishing especially for women in the early stages of their career.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is in this setting that concerns have been raised that research and expert reporting on the COVID-19 pandemic has disproportionately involved men as scientific authors. For example, women submitted fewer manuscripts overall, were less available for peer review [6][7][8] and attended fewer funding panel meetings. 7 Also, women first authorship was significantly reduced on preprints and publications about COVID-19 in the USA 9 10 and globally.…”
Section: Introductionmentioning
confidence: 99%
“…A large study of the top 50 medical imaging journals evaluating authorship of submissions from March to May of 2018 ( n = 2,238), 2019 ( n = 2,355) and 2020 ( n = 2,480) showed female first authorship and last authorship in 2018–2019 were 31.6% and 19.3%, respectively, and 32.3% and 20.7% in 2020, respectively [ 10 ]. Another recent study evaluating gender differences in the authorship of publications in the Journal of the American College of Radiology during April to October of 2019 versus the same period in 2020 showed female first authorship being 45% and 39%, respectively, and female corresponding authorship being 42.4% and 37.4%, respectively [ 11 ]. Of note, female last authorship in Pediatric Radiology was higher than the overall frequency in the large-scale study and closer to the frequency of corresponding authorship in the Journal of the American College of Radiology study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends were shown for radiology. One study showed an overall decreased proportion of female first author submissions during the 2020 study period in comparison to the same period in 2019, as well as a statistically significant lower proportion of female first authors for COVID-19 related publications in the Journal of the American College of Radiology [ 11 ]. This observation was hypothesized to be potentially disadvantageous to academic advancement for women in radiology, especially those in their early career and more likely to have non-work-related responsibilities that were heightened during the early phase of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation